Development of a performance evaluation form for secondary school principals - Tongbumrung, Renu 1939-
This study developed a performance evaluation form for secondary school principals in the Division of City Schools, Quezon City. The data were gathered by asking principals, assistants to the principals, supervisors and the Superintendent in the Division of City Schools, Quezon City to respond to a performance evaluation form questionnaire.